Impact of dimension-8 SMEFT operators on diboson productions - Céline Degrande; Hao-Lin Li (Journal of High Energy Physics, 2023)
Abstract We for the first time identify all the dimension-8 (dim-8) SMEFT operators that can have an interference with the SM with E 4/Λ4 enhancement in the high energy limit for the processes q q ¯ → WW / WZ $$ q\overline{q}→ WW/ WZ $$ . Our results therefore explicitly show that the non-interference observed for the dimension-six does not extend to dimension-eight. We compute the contributions of those dimension-8 operators to the cross-section at the 14 TeV Large Hadron Collider and compare the results with dimension-6 (dim-6) originated corrections at the order of dim-6-SM interference and dim-6 squared. We find one (two) dim-8 operator(s) can generate amplitudes of a similar order of magnitude compared with their dim-6 squared counterparts assuming unity dimensionless Wilson coefficients. During the study, new non-interference scenarios are found due to the selection rule of angular momentum as well as strong suppression due to the symmetric initial state for the proton-proton collider.